A high-efficiency carbon dioxide electroreduction catalyst and preparation method thereof

By forming an atomic alloy structure of a transition metal and a second metal on the nitrogen-doped carbon nanotube support, the existing catalysts have been solved, and the efficient and economical carbon dioxide electrical reduction effect is achieved.

CN119776894AInactive Publication Date: 2025-04-08GUANGZHOU CITY POLYTECHNIC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510015623.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing carbon dioxide electroreduction catalysts have problems such as low catalytic activity, poor selectivity and insufficient stability, which are difficult to meet the needs of industrial applications.

Method used

Atomic alloy structures of atomic dispersed transition metal elements (such as cobalt, nickel, manganese) and a second metal elements (such as iron, copper, zinc) on the nitrogen-doped carbon nanotube support are used, combined with multifunctional additives, and through specific microstructure and chemical treatment steps, a catalyst with high catalytic activity, high selectivity and good stability is formed.

Benefits of technology

It significantly improves catalytic activity and selectivity, reduces the energy input required for the reaction, improves energy utilization efficiency, extends the service life of the catalyst, reduces production costs and complexity, and promotes the industrial application of carbon dioxide electroreduction technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776894A_ABST
    Figure CN119776894A_ABST
Patent Text Reader

Abstract

The present invention relates to an efficient carbon dioxide electroreduction catalyst and a preparation method thereof. In order to overcome the defects of existing catalysts, an innovative design is adopted: the transition metal is dispersed at the atomic level on nitrogen-doped carbon nanotubes, a second metal is introduced to produce a synergistic effect, the electronic structure and adsorption performance are optimized, and the catalytic activity and selectivity are improved; the microstructure is precisely regulated by combining the template method with self-assembly, hierarchical porosity and specific morphology are constructed to promote material transfer; and multifunctional additives are added to enhance stability. During preparation, the catalyst undergoes the steps of precursor solution preparation, carrier treatment and impregnation, template self-assembly, high-temperature pyrolysis, and post-treatment activation. The catalyst has significant advantages in carbon dioxide electroreduction, exhibits high activity and selectivity in a wide potential range, and is stable in long-term electrolysis, providing an efficient solution for the resource utilization of carbon dioxide, and has great industrial application and environmental value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalytic materials, and in particular relates to the research, development and preparation of carbon dioxide electroreduction catalysts. Background Art

[0002] In today's era, the rapid development of global industrialization is like a double-edged sword. While it brings economic prosperity, it also causes a sharp increase in carbon dioxide emissions.

[0003] Among the many strategies to address the issue of carbon dioxide emissions, carbon dioxide electroreduction reaction technology stands out and has become a hot research area. Based on electrochemical principles, this technology can use electricity to convert carbon dioxide molecules into chemicals or fuels with higher economic value under relatively mild reaction conditions. Carbon monoxide can be used for chemical synthesis, formic acid has potential application value in the field of fuel cells, and methanol is an important clean energy substitute. This technical path of turning carbon dioxide into treasure is not only expected to achieve the goal of reducing carbon dioxide emissions, but also to create new economic growth points and bring new development opportunities to the energy and chemical industries. It is of great significance to the construction of a sustainable carbon circular economic system.

[0004] Currently available carbon dioxide electroreduction catalysts are far from meeting the stringent requirements of industrial applications, and there are many key issues that need to be addressed. From the perspective of catalytic activity, most traditional catalysts require a high overpotential when driving carbon dioxide electroreduction reactions, which means that a large amount of electrical energy is required to overcome the reaction energy barrier, greatly reducing the energy efficiency of the entire conversion process. Some common metal catalysts require an overpotential of hundreds of millivolts or even higher to achieve a certain conversion rate, which will undoubtedly bring high energy costs in large-scale industrial production, greatly limiting the economic feasibility of the technology.

[0005] In terms of selectivity, the performance of existing catalysts is also unsatisfactory. Since the carbon dioxide electroreduction reaction process is relatively complex, involving multiple electron transfer steps and multiple possible reaction pathways, traditional catalysts often lack the ability to accurately control specific reaction pathways, resulting in the generation of multiple by-products. The presence of these by-products not only reduces the purity and yield of the target product, but also makes the subsequent separation and purification processes complicated and cumbersome, further increasing production costs and process difficulties. Taking some metal oxide catalysts as an example, when conducting carbon dioxide electroreduction reactions, in addition to generating the target product carbon monoxide, a variety of by-products such as hydrogen and methane are also produced, so that the selectivity of carbon monoxide can usually only be maintained at a low level, and it is difficult to meet the purity and yield requirements required for industrial production.

[0006] The stability issue has become a major bottleneck for existing carbon dioxide electroreduction catalysts. During long-term electrolysis, the microstructure of the catalyst is prone to change, and the active sites are prone to agglomeration, which will lead to a significant reduction in the number of effective active sites, thereby rapidly decreasing the catalytic activity. At the same time, intermediates or impurities produced during the reaction may be adsorbed on the catalyst surface, occupying active sites, causing catalyst poisoning and causing it to lose its catalytic ability. In addition, during repeated redox cycles, the catalyst may also experience structural collapse or loss of active components, further shortening its service life. After several hours of continuous electrolysis, the catalytic activity of some nanometal catalysts will drop to less than half of the initial activity. This poor stability requires frequent replacement or regeneration of the catalyst, greatly increasing the operating cost and complexity of industrial production, and seriously hindering the large-scale industrial promotion of carbon dioxide electroreduction technology.

[0007] In view of the severe problems currently faced by carbon dioxide electroreduction catalysts, there is an urgent need to develop a new carbon dioxide electroreduction catalyst with high catalytic activity, high selectivity and good stability to break through the limitations of existing technologies and promote carbon dioxide electroreduction technology from laboratory research to industrial practical applications, providing practical technical solutions for global response to climate change and sustainable development. This has become an urgent and arduous task facing scientific researchers in this field, and it has great practical significance and far-reaching strategic value. Summary of the invention

[0008] The present invention aims to solve the key problems of low catalytic activity, poor selectivity and insufficient stability of existing carbon dioxide electroreduction catalysts, so as to meet the actual needs of efficient resource utilization of carbon dioxide and promote the industrial application of carbon dioxide electroreduction technology.

[0009] The active component of the catalyst comprises a transition metal element dispersed at the atomic level on a nitrogen-doped carbon nanotube carrier, wherein the transition metal element is one or more of cobalt, nickel, and manganese, and the catalyst also contains a second metal element forming an atomic alloy structure with the transition metal, wherein the second metal element is one or more of iron, copper, and zinc, and a multifunctional additive accounting for 0.1%-5% of the total mass of the catalyst, wherein the multifunctional additive is one or more of lanthanum oxide, cerium oxide, lanthanum boride, and magnesium boride. In the atomic alloy structure, the atomic ratio of the transition metal to the second metal is 1:0.2-1:1, and through X-ray photoelectron spectroscopy (XPS) analysis, the electronic binding energy of each metal element in the alloy structure undergoes a specific shift, indicating that the electronic structure has changed, thereby optimizing the catalytic performance of the carbon dioxide electroreduction reaction.

[0010] The nitrogen-doped carbon nanotubes have a nitrogen content of 5%-15%, a tube diameter of 10-50nm, a length of 1-10μm, and a surface oxygen-containing functional group density of 0.5-2mmol / g. They interact strongly with active metal atoms through chemical bonding or electron transfer, so that the electron cloud density of the active site is regulated within a specific range, thereby enhancing the stability and catalytic activity of the active site.

[0011] The catalyst has a hierarchical porous structure, wherein the macropore size is 80-300nm, accounting for 10%-30% of the total pore volume, the mesopore size is 5-30nm, accounting for 40%-60% of the total pore volume, and the micropore size is less than 2nm, accounting for 20%-40% of the total pore volume, so as to promote efficient diffusion and transport of reactants and products. - The catalyst has a specific morphology, nanosheets with a thickness of 5-50nm, nanowires with a diameter of 10-100nm, or nanoparticles with a particle size of 20-200nm, so as to increase the exposure of active sites and the adsorption capacity of reactants, and its specific surface area is 500-1500m 2 / g.

[0012] The precursor solution accurately weighs transition metal salts, cobalt acetylacetonate, nickel nitrate, manganese sulfate, a second metal salt, ferrous chloride, copper sulfate, zinc nitrate, nitrogen source compounds, melamine, urea, cyanamide, and multifunctional auxiliary agent precursors, lanthanum nitrate, cerium nitrate, boric acid, and boron magnesium alloy powder in proportion, and dissolves them in deionized water containing 0.3-0.8g / mL surfactant sodium dodecyl sulfate, and stirs for 1-3 hours at 40-60°C to form a uniform mixed solution, wherein the concentration of each metal ion is 0.05-0.5mol / L, the concentration of the nitrogen source compound is 0.5-2mol / L, and the concentration of the multifunctional auxiliary agent precursor is accurately adjusted according to the auxiliary agent content in the target catalyst. The purity of the transition metal salt, the second metal salt, the nitrogen source compound, and the multifunctional auxiliary agent precursor is not less than 99%, and when preparing the precursor solution, it is necessary to operate in a glove box to control the oxygen and water contents to be less than 0.1ppm to ensure the stability and accuracy of each component and avoid the influence of impurities on the catalyst performance.

[0013] The carrier pretreatment and impregnation are as follows: the commercial carbon nanotubes are acidified with a 2-5 mol / L nitric acid solution at 60-80°C for 2-6 hours, then washed with deionized water until neutral, the treated carbon nanotubes are added to the above precursor solution at a ratio of 0.3-0.8 g / mL, ultrasonicated at an ultrasonic power of 200-500 W for 40-60 minutes, and then impregnated at 25-35°C for 15-20 hours to allow the metal ions and additives to be fully adsorbed on the surface of the carbon nanotubes.

[0014] The template self-assembly and structure regulation: add a template agent to the impregnated system, the template agent is nano-silicon dioxide with a particle size of 50-200nm or polystyrene microspheres with a diameter of 100-500nm, add at a mass ratio of 0.5-2:1 between the template agent and the carbon nanotube, perform a hydrothermal or solvothermal reaction at 140-160°C for 16-20 hours, and form a composite with a specific microstructure, and control the pH value of the solution to be 8-10 during the reaction. In the template self-assembly and structure regulation step, after the hydrothermal or solvothermal reaction is completed, the composite is collected by centrifugation, the centrifugal speed is 8000-12000rpm, the centrifugal time is 10-20 minutes, and then washed alternately with anhydrous ethanol and deionized water for 3-5 times to remove unreacted template agent and other impurities, so as to ensure the purity and structural integrity of the composite.

[0015] The high temperature pyrolysis and atomic dispersion: the above-mentioned complex is heated to 750-850°C at a heating rate of 6-8°C / min under an argon atmosphere, and is kept warm for 2.5-3.5 hours for pyrolysis. During the pyrolysis process, the argon flow rate is maintained at 30-50mL / min, so that the metal salt and the auxiliary agent precursor are decomposed and react with the nitrogen source and the carbon nanotubes in a complex chemical reaction to form a catalyst structure with atomically dispersed bimetallic active sites loaded on nitrogen-doped carbon nanotubes and having a specific microstructure. In the high temperature pyrolysis step, the heating program of the pyrolysis furnace needs to be precisely controlled. When the temperature is raised to the range of 400-600°C, the heating rate can be appropriately reduced to 4-6°C / min to ensure the slow decomposition of the template and some organic matter, and avoid the destruction of the catalyst structure due to the rapid release of gas. At the same time, during the insulation stage, the temperature uniformity in the pyrolysis furnace needs to be monitored and regulated to ensure that the temperature deviation of the sample during the pyrolysis process does not exceed ±5°C, and the consistency and stability of the catalyst performance are guaranteed.

[0016] The post-treatment and activation: the pyrolyzed sample is pickled with a 0.4-0.6mol / L hydrochloric acid solution at 40-60°C for 1.5-2.5 hours, and then reduced at 320-380°C for 1.2-1.8 hours under a hydrogen atmosphere at a hydrogen flow rate of 20-40mL / min to further activate the active sites of the catalyst and improve its catalytic performance. In the post-treatment and activation step, the pickled sample needs to be fully washed with deionized water to neutrality, and then dried in a vacuum drying oven at 60-80°C for 10-15 hours to remove moisture and residual acid radical ions, to ensure the stability and activity of the catalyst in the subsequent hydrogen reduction process, and at the same time, during the hydrogen reduction process, the purity of the hydrogen needs to be detected and controlled to ensure that the impurity gas content in the hydrogen is less than 0.01%, to prevent the impurity gas from poisoning the catalyst, and to ensure the activation effect and performance of the catalyst.

[0017] The above technical solution can bring the following significant technical effects:

[0018] 1. Significantly improve catalytic activity: Atomically dispersed transition metal active sites greatly increase the contact area between the catalyst and the carbon dioxide molecules, enabling it to more efficiently adsorb and activate carbon dioxide molecules. The bimetallic synergistic effect further optimizes the electronic structure and reduces the energy barrier of the reaction, thereby significantly improving the catalytic reaction rate. In the carbon dioxide electroreduction reaction, compared with traditional catalysts, the catalyst of the present invention can shift the starting potential positively by more than [X] mV. At the same potential, the reaction current density is increased by more than [X] times, which greatly enhances the catalytic activity, effectively reduces the energy input required for the reaction, and improves energy utilization efficiency, providing a more economical and feasible way for large-scale conversion of carbon dioxide.

[0019] 2. Accurately enhance product selectivity: Through carefully designed active site structure and microstructure regulation, the catalyst can accurately guide the carbon dioxide electroreduction reaction toward the direction of generating specific target products (such as carbon monoxide, formic acid, methanol, etc.). For example, for the generation of carbon monoxide, its Faraday efficiency can be maintained above [X]% over a wide potential range, which is more than [X] percentage points higher than traditional catalysts. This means that during the reaction, more carbon dioxide can be converted into the target product, greatly reducing the generation of by-products, reducing the cost and complexity of subsequent product separation and purification, and significantly improving the economic benefits of carbon dioxide resource utilization, providing a more selective method for the green synthesis of chemical raw materials.

[0020] 3. Significantly improved stability: The stable atomic-level alloy structure effectively prevents the aggregation and loss of active metals during the reaction process, and the strong interaction between the nitrogen-doped carbon nanotube carrier and the active sites further enhances the structural stability of the catalyst. After a long period of electrolysis testing, the catalyst of the present invention has a decay rate of catalytic activity and product selectivity of less than [X]% after [X] hours of continuous operation, while traditional catalysts often show a significant performance decline within a few hours under the same conditions. This excellent stability enables the catalyst to operate stably for a long time in an industrial production environment, reducing the cost and downtime caused by frequent catalyst replacement, improving production efficiency, and providing solid and reliable technical support for the industrial application of carbon dioxide electroreduction technology, which has strongly promoted the development of the carbon recycling economy. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The process diagram of the method for preparing the high-efficiency carbon dioxide electroreduction catalyst of the present invention is shown in FIG.

[0022] Figure 2 Comparison diagram of the embodiment of the high-efficiency carbon dioxide electroreduction catalyst of the present invention DETAILED DESCRIPTION

[0023] The following will be combined with the attached embodiment of the present invention Figure 1 , the technical scheme in the embodiment of a high-efficiency carbon dioxide electroreduction catalyst and a preparation method thereof of the present invention is clearly and completely described. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Embodiment 1:

[0025] Preparation of precursor solution: In a glove box (oxygen and water content less than 0.1ppm), weigh 0.5mmol cobalt acetylacetonate (purity 99.5%), 0.2mmol ferrous chloride (purity 99.2%), 1.0g melamine (purity 99.8%), 0.1mmol lanthanum nitrate (purity 99.6%), dissolve in 50ml deionized water containing 0.5g sodium dodecyl sulfate, stir at 50°C for 2 hours to form a mixed solution, in which the cobalt ion concentration is 0.01mol / L, the ferrous ion concentration is 0.004mol / L, the nitrogen source compound concentration is 1mol / L, and the lanthanum ion concentration is accurately adjusted according to the content of the additive in the target catalyst.

[0026] Support pretreatment and impregnation: 0.5 g of commercial carbon nanotubes were acidified with 3 mol / L nitric acid solution at 70°C for 4 hours, and then washed with deionized water until neutral. The treated carbon nanotubes were added to the above precursor solution, ultrasonicated at 300 W for 50 minutes, and then impregnated at 30°C for 18 hours.

[0027] Template self-assembly and structure regulation: 0.3 g of nano-silica template with a particle size of 100 nm was added to the impregnated system, and a hydrothermal reaction was carried out at 150°C for 18 hours. During the reaction, the pH value of the solution was controlled to 9 with sodium hydroxide solution. After the reaction, the solution was centrifuged at 10,000 rpm for 15 minutes, and then washed alternately with anhydrous ethanol and deionized water for 4 times.

[0028] High-temperature pyrolysis and atomic dispersion: The above-mentioned composite was heated to 800°C at a heating rate of 7°C / min in an argon atmosphere. When the temperature reached 500°C, the heating rate was reduced to 5°C / min and the composite was kept at this temperature for 3 hours for pyrolysis. The argon flow rate was maintained at 40 mL / min during the pyrolysis process, and the temperature deviation of the sample during the pyrolysis process was ensured to be no more than ±5°C by a temperature control system.

[0029] Post-treatment and activation: The pyrolyzed sample was acid-washed with 0.5 mol / L hydrochloric acid solution at 50°C for 2 hours, then fully washed with deionized water until neutral, and dried in a vacuum drying oven at 70°C for 12 hours. After that, it was reduced at 350°C for 1.5 hours under a hydrogen atmosphere at a hydrogen flow rate of 30 mL / min.

[0030] In the carbon dioxide electroreduction reaction, a three-electrode system was used, with the glassy carbon electrode modified with the catalyst as the working electrode, the saturated calomel electrode as the reference electrode, and the platinum electrode as the counter electrode, and the test was carried out in a 0.2 mol / L carbon dioxide saturated potassium bicarbonate solution. At a potential of -0.8 V (vs. RHE), the Faraday efficiency of carbon monoxide reached 82%, and the Faraday efficiency of formic acid was 10%. During the 20-hour constant potential electrolysis process, the current density only decayed by 8%, and the catalytic activity and selectivity did not decrease significantly, showing the advantages of high activity, high selectivity and good stability.

[0031] Example 2

[0032] Preparation of precursor solution: Weigh 0.4 mmol nickel nitrate (purity 99.3%), 0.3 mmol copper sulfate (purity 99.4%), 1.2 g urea (purity 99.7%), and 0.08 mmol boric acid (purity 99.5%), dissolve in 60 ml deionized water containing 0.6 g sodium dodecyl sulfate, stir at 45 ° C for 2.5 hours, and adjust the concentration of each metal ion and nitrogen source compound according to the target catalyst.

[0033] Carrier pretreatment and impregnation: 0.6 g of carbon nanotubes were acidified with 4 mol / L nitric acid solution at 65°C for 3 hours, and then washed and added with precursor solution in proportion, ultrasonicated for 45 minutes (ultrasonic power 400 W), and impregnated at 28°C for 16 hours.

[0034] Template self-assembly and structural regulation: add 0.4g polystyrene microsphere template with a diameter of 300nm, solvothermally react at 145℃ for 19 hours, control the pH value to 8.5, centrifuge (11000rpm, 18 minutes) and wash after the reaction. -Step 4: High temperature pyrolysis and atomic dispersion-under argon protection, heat to 830℃ at 6.5℃ / min, reduce to 4.5℃ / min at 500℃, keep warm for 2.8 hours, argon flow rate 35mL / min, control temperature deviation, post-treatment and activation: pickle with 0.55mol / L hydrochloric acid for 1.8 hours (55℃), wash and dry, and reduce at 360℃ for 1.6 hours at a hydrogen flow rate of 25mL / min.

[0035] Under the same test conditions, at a potential of -0.7V (vs.RHE), the Faradaic efficiency of formic acid can reach 73%, the Faradaic efficiency of carbon monoxide is 15%, and the current density decays by 6% after 18 hours of electrolysis, which reflects good catalytic performance and stability, and has high selectivity for the production of formic acid.

[0036] Embodiment 3:

[0037] Preparation of precursor solution: Take 0.3 mmol manganese sulfate (purity 99.4%), 0.25 mmol zinc nitrate (purity 99.3%), 0.8 g cyanamide (purity 99.6%), 0.06 mmol cerium nitrate (purity 99.5%), dissolve in 40 ml water containing 0.4 g sodium dodecyl sulfate, and stir at 55°C for 1.5 hours.

[0038] Support pretreatment and impregnation: 0.4 g of carbon nanotubes were treated by acidification at 75° C. and 2.5 mol / L nitric acid for 5 hours, and then the precursor solution was added, ultrasonicated for 55 minutes (350 W), and impregnated at 26° C. for 20 hours.

[0039] Template self-assembly and structure regulation: add 0.25 g of 80 nm nano-silica, hydrothermal at 155° C. for 17 hours, control the pH at 9.5, and wash by centrifugation (9000 rpm, 20 minutes).

[0040] High temperature pyrolysis and atomic dispersion: in argon, heat up to 780°C at 7.5°C / min, decrease from 450°C to 5.5°C / min, keep warm for 3.2 hours, argon 45mL / min, temperature control deviation.

[0041] Post-treatment and activation: pickling with 0.45mol / L hydrochloric acid at 60℃ for 2.2 hours, washing and drying, and reduction with hydrogen at 35mL / min and 340℃ for 1.4 hours.

[0042] Tests show that at a potential of -0.9 V (vs. RHE), the Faradaic efficiency of methanol reaches 12%, and the Faradaic efficiency of carbon monoxide is 60%. After 22 hours of electrolysis, the current density decays by 9%, indicating that there is a certain selectivity for methanol production and the overall performance is stable, which is better than the performance of traditional catalysts under this condition.

[0043] Embodiment 4:

[0044] Preparation of precursor solution: weigh 0.45mmol cobalt acetylacetonate (99.6%), 0.15mmol ferrous chloride (99.3%), 0.1mmol copper sulfate (99.4%), 1.0g melamine (99.7%), 0.05mmol lanthanum boride (99.5%), dissolve in 50ml water containing 0.5g sodium dodecyl sulfate, and stir at 40°C for 3 hours.

[0045] Support pretreatment and impregnation: 0.5 g of carbon nanotubes were treated at 60° C. and 3.5 mol / L nitric acid for 4.5 hours, then the precursor was added, ultrasonicated for 40 minutes (450 W), and then immersed at 32° C. for 17 hours.

[0046] Template self-assembly and structural regulation: add 0.35 g of polystyrene microspheres with a diameter of 200 nm, solvotherm at 140° C. for 20 hours, pH 8, and wash by centrifugation (10,000 rpm, 16 minutes).

[0047] High temperature pyrolysis and atomic dispersion: argon 6℃ / min to 820℃, 480℃ to 5℃ / min, hold for 2.6 hours, argon 38mL / min, temperature control.

[0048] Post-treatment and activation: pickling with 0.6 mol / L hydrochloric acid at 45°C for 1.6 hours, followed by hydrogenation at 28 mL / min and 370°C for 1.3 hours.

[0049] At a potential of -0.75 V (vs. RHE), the Faradaic efficiency of carbon monoxide reached 78%, formic acid 12%, and the electrolysis current density dropped by 7% after 20 hours, showing good activity, selectivity and stability, and the multi-metal combination effect was significant.

[0050] Embodiment 5:

[0051] Preparation of precursor solution: Take 0.35mmol nickel nitrate (99.4%), 0.2mmol zinc nitrate (99.3%), 1.1g urea (99.8%), 0.07mmol cerium nitrate (99.6%), and 0.03mmol magnesium boride (99.5%), and stir in 50ml water containing 0.5g sodium dodecyl sulfate at 50°C for 2 hours.

[0052] Carrier pretreatment and impregnation: 0.55 g carbon nanotubes were acidified at 75° C. and 4 mol / L nitric acid for 3.5 hours, then placed into the precursor, ultrasonicated for 50 minutes (380 W), and immersed at 27° C. for 19 hours.

[0053] Template self-assembly and structure regulation: add 0.3 g of 120 nm nano-silica, hydrothermal at 150°C for 18 hours, pH 9, and wash by centrifugation (10500 rpm, 17 minutes).

[0054] High temperature pyrolysis and atomic dispersion: argon 7°C / min to 800°C, 500°C to 4.5°C / min, maintain for 3 hours, argon 42mL / min, temperature control.

[0055] Post-treatment and activation: pickling with 0.5 mol / L hydrochloric acid at 50°C for 2 hours, washing and vacuum drying at 75°C for 10 hours, hydrogenation at 32 mL / min and 350°C for 1.5 hours.

[0056] At a potential of -0.85 V (vs. RHE), the Faradaic efficiency of formic acid is 68%, that of carbon monoxide is 18%, and the electrolysis current density decays by 5% after 16 hours, indicating that the catalyst has good selectivity for formic acid and excellent stability under this formulation.

[0057] Embodiment 6:

[0058] Preparation of precursor solution: Weigh 0.25mmol manganese sulfate (99.5%), 0.15mmol ferrous chloride (99.2%), 0.1mmol copper sulfate (99.3%), 0.9g melamine (99.6%), and 0.04mmol lanthanum nitrate (99.4%), dissolve in 45ml water containing 0.45g sodium dodecyl sulfate, and stir at 45°C for 2.5 hours.

[0059] Carrier pretreatment and impregnation: 0.45 g carbon nanotubes were treated at 65° C. and 3 mol / L nitric acid for 4 hours, then the precursor was added, ultrasonicated for 45 minutes (420 W), and immersed at 30° C. for 18 hours.

[0060] Template self-assembly and structural regulation: add 0.28 g of polystyrene microspheres with a diameter of 400 nm, solvotherm at 145° C. for 19 hours, pH 8.5, and wash by centrifugation (9500 rpm, 18 minutes).

[0061] High temperature pyrolysis and atomic dispersion: Argon 6.5°C / min to 780°C, 450°C to 5°C / min, hold for 2.8 hours, Argon 36mL / min, temperature control.

[0062] Post-treatment and activation: pickling with 0.55 mol / L hydrochloric acid at 55°C for 1.8 hours, washing and vacuum drying at 70°C for 13 hours, hydrogenation at 26 mL / min and 360°C for 1.4 hours.

[0063] At a potential of -0.9V (vs.RHE), the Faradaic efficiency of methanol is 10%, that of carbon monoxide is 65%, and the electrolysis current density decays by 8% in 20 hours, indicating that the catalyst has a certain selectivity for methanol under specific conditions and good stability. It has obvious advantages over traditional catalysts and provides a more efficient and stable solution for carbon dioxide electroreduction.

[0064] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A highly efficient carbon dioxide electroreduction catalyst, characterized in that: - The active component includes a transition metal element dispersed at the atomic level on a nitrogen-doped carbon nanotube carrier, wherein the transition metal element is one or more of cobalt, nickel, and manganese, and the catalyst also contains a second metal element that forms an atomic-level alloy structure with the transition metal, wherein the second metal element is one or more of iron, copper, and zinc, and a multifunctional additive accounting for 0.1%-5% of the total mass of the catalyst, wherein the multifunctional additive is one or more of lanthanum oxide, cerium oxide, lanthanum boride, and magnesium boride; - The nitrogen content of the nitrogen-doped carbon nanotube is 5%-15%, the tube diameter is 10-50nm, the length is 1-10μm, and the oxygen-containing functional group density on its surface is 0.5-2mmol / g, and it is produced by chemical bonding or electron transfer with the active metal atoms. The catalyst has a hierarchical porous structure, wherein the macropore size is 80-300nm, accounting for 10%-30% of the total pore volume, the mesopore size is 5-30nm, accounting for 40%-60% of the total pore volume, and the micropore size is less than 2nm, accounting for 20%-40% of the total pore volume, so as to promote efficient diffusion and transport of reactants and products; The catalyst has a specific morphology, with a nanosheet with a thickness of 5-50nm, a nanowire with a diameter of 10-100nm, or a nanoparticle with a particle size of 20-200nm, so as to increase the exposure of the active site and the adsorption capacity of the reactants, and its specific surface area is 500-1500m 2 / g.

2. The catalyst according to claim 1, characterized in that: In the atomic-level alloy structure, the atomic ratio of the transition metal to the second metal is 1:0.2-1:1, and through X-ray photoelectron spectroscopy (XPS) analysis, the electron binding energy of each metal element in the alloy structure undergoes a specific shift, indicating that the electronic structure has changed, thereby optimizing the catalytic performance of the carbon dioxide electroreduction reaction.

3. The method for preparing a high-efficiency carbon dioxide electro-reduction catalyst according to any one of claims 1 to 2, characterized in that: The following steps are involved: s301. Preparation of precursor solution: accurately weigh transition metal salt, cobalt acetylacetonate, nickel nitrate, manganese sulfate, second metal salt, ferrous chloride, copper sulfate, zinc nitrate, nitrogen source compound, melamine, urea, cyanamide, and multifunctional auxiliary agent precursor, lanthanum nitrate, cerium nitrate, boric acid, boron magnesium alloy powder according to proportion, dissolve them in deionized water containing 0.3-0.8g / mL surfactant sodium dodecyl sulfate, stir at 40-60°C for 1-3 hours to form a uniform mixed solution, the concentration of each metal ion is 0.05-0.5mol / L, the concentration of the nitrogen source compound is 0.5-2mol / L, and the concentration of the multifunctional auxiliary agent precursor is accurately prepared according to the auxiliary agent content in the target catalyst; s302. Carrier pretreatment and impregnation: The commercial carbon nanotubes are acidified with 2-5 mol / L nitric acid solution at 60-80°C for 2-6 hours, then washed with deionized water until neutral, the treated carbon nanotubes are added to the above precursor solution at a ratio of 0.3-0.8 g / mL, ultrasonicated at an ultrasonic power of 200-500 W for 40-60 minutes, and then impregnated at 25-35°C for 15-20 hours to allow the metal ions and additives to be fully adsorbed on the surface of the carbon nanotubes; s303. Template self-assembly and structural regulation: adding a template agent to the impregnated system, wherein the template agent is nano-silicon dioxide with a particle size of 50-200 nm or polystyrene microspheres with a diameter of 100-500 nm, and adding the template agent to the carbon nanotubes at a mass ratio of 0.5-2:1, and performing a hydrothermal or solvothermal reaction at 140-160° C. for 16-20 hours to form a composite with a specific microstructure, and controlling the pH value of the solution to be 8-10 during the reaction; s304. High temperature pyrolysis and atomic dispersion: The above-mentioned complex is heated to 750-850°C at a heating rate of 6-8°C / min under an argon atmosphere, and kept at this temperature for 2.5-3.5 hours for pyrolysis. During the pyrolysis process, the argon flow rate is maintained at 30-50mL / min, so that the metal salt and the auxiliary agent precursor are decomposed and undergo complex chemical reactions with the nitrogen source and the carbon nanotubes, forming a catalyst structure with atomically dispersed bimetallic active sites loaded on the nitrogen-doped carbon nanotubes and having a specific microstructure; s305. Post-treatment and activation: The pyrolyzed samples were acid-washed with 0.4-0.6 mol / L hydrochloric acid solution at 40-60°C for 1.5-2.5 hours, and then reduced at 320-380°C for 1.2-1.8 hours under a hydrogen atmosphere at a hydrogen flow rate of 20-40 mL / min to further activate the active sites of the catalyst and improve its catalytic performance.

4. The preparation method according to claim 3, characterized in that: The purity of the transition metal salt, the second metal salt, the nitrogen source compound and the multifunctional auxiliary agent precursor is not less than 99%, and when preparing the precursor solution, the operation must be carried out in a glove box to control the oxygen and water contents to be less than 0.1ppm to ensure the stability and accuracy of each component and avoid the influence of impurities on the catalyst performance.

5. The preparation method according to claim 3, characterized in that: In the template self-assembly and structure regulation step, after the hydrothermal or solvothermal reaction is completed, the complex is collected by centrifugation at a speed of 8000-12000 rpm for 10-20 minutes, and then washed alternately with anhydrous ethanol and deionized water for 3-5 times to remove unreacted template agent and other impurities to ensure the purity and structural integrity of the complex.

6. The preparation method according to claim 3, characterized in that: In the high-temperature pyrolysis step, the temperature rise program of the pyrolysis furnace needs to be precisely controlled. When the temperature rises to the 400-600°C range, the heating rate can be appropriately reduced to 4-6°C / minute to ensure the slow decomposition of the template and some organic matter, and avoid the destruction of the catalyst structure due to rapid gas release. At the same time, during the insulation stage, the temperature uniformity in the pyrolysis furnace needs to be monitored and regulated to ensure that the temperature deviation of the sample during the pyrolysis process does not exceed ±5°C, thereby ensuring the consistency and stability of the catalyst performance.

7. The preparation method according to claim 3, characterized in that: In the post-treatment and activation steps, the acid-washed sample needs to be fully washed with deionized water to neutrality, and then dried in a vacuum drying oven at 60-80°C for 10-15 hours to remove moisture and residual acid ions to ensure the stability and activity of the catalyst in the subsequent hydrogen reduction process. At the same time, during the hydrogen reduction process, the purity of hydrogen needs to be detected and controlled to ensure that the impurity gas content in the hydrogen is less than 0.01% to prevent the impurity gas from poisoning the catalyst and ensure the activation effect and performance of the catalyst.